1991
DOI: 10.1002/hrm.3930300103
|View full text |Cite
|
Sign up to set email alerts
|

The impact of future demographic shifts on the employment of older workers

Abstract: This article argues that future demographic shifts will alter the supply of older workers and the demand for their services. Research conducted by the authors, shows that a significant percentage of older workers not currently working would like to work and that older workers can be as cost effective and capable as younger workers. Recommendations for facilitating the greater employment of older workers conclude the article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…There has been considerable discussion regarding the physical capacity of older workers to maintain their health and productivity on the job [Barth and McNaught, 1991;Ilmarinen, 1997;Naegele, 1999;Wegman, 1999]. An issue of particular concern has been the increased risk of work injury and subsequent disability due to age-associated decrements in cognitive function, health, and recuperative ability [Mitchell, 1988;Anonymous, 1993;Laflamme and Menckel, 1995;Zwerling et al, 1996;Benjamin and Pransky, 2000].…”
Section: Introductionmentioning
confidence: 99%
“…There has been considerable discussion regarding the physical capacity of older workers to maintain their health and productivity on the job [Barth and McNaught, 1991;Ilmarinen, 1997;Naegele, 1999;Wegman, 1999]. An issue of particular concern has been the increased risk of work injury and subsequent disability due to age-associated decrements in cognitive function, health, and recuperative ability [Mitchell, 1988;Anonymous, 1993;Laflamme and Menckel, 1995;Zwerling et al, 1996;Benjamin and Pransky, 2000].…”
Section: Introductionmentioning
confidence: 99%
“…A number of factors also appear likely to affect employment opportunities for older workers in the near future (Barth & McNaught, 1991). For example, most American jobs no longer involve heavy physical demands and have become suitable for older workers.…”
mentioning
confidence: 99%
“…In addition, the pressures of a globalizing economy place increased pressure on employers to retain skilled workers, and older workers in recent decades have increased dramatically in educational level and skill acquisition. Several supply-side factors also suggest that larger numbers of older workers will be available in the near future (Barth & McNaught, 1991). For example, the baby-boomer generation is fast approaching this age range, and they are healthier than previous cohorts.…”
mentioning
confidence: 99%
“…Specifically, Yankelovich, Skelly, and White found that healthcare costs were about the same in a comparison of 30-year-old males, women with dependents, and 65-year-old retirees. In addition, another study reveals that the frequency of occupational injuries declined with age, apparently because experience helps workers avoid accidents [21]- [23].…”
Section: Employment Issuesmentioning
confidence: 99%